Influence of weaning weight and growth during the first week postweaning on subsequent pig performance - L J Kats; Michael D Tokach; Robert D Goodband; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1992)
A total of 1,350 pigs was used in three growth trials to determine the influence of weaning weight and average daily gain during the first week postweaning on subsequent growth performance. Average initial weight and age were 13.7 lb and 21 d, respectively. Pigs were weighed on d 0, 7, 28, and 56 postweaning in all three trials. Pigs were also weighed at market in trial 1. Weaning weight influenced postweaning growth performance such that each additional pound at weaning translated into approximately 2 lb by d 56 postweaning and 4 lb at market. These results indicate the importance of maximizing milk production during lactation to increase litter weaning weights. Average daily gain during the first week postweaning also had a major impact on subsequent growth performance. Pigs that gained greater than .5 Ibid during the first week postweaning were 17 Ib heavier at market than pigs that lost weight during the first week postweaning. These results provide further evidence that nutritional programs designed to increase starter pig performance also influence performance during the subsequent grower and finisher phases.; Swine Day, Manhattan, KS, November 19, 1992
Keywords: Swine day; 1992; Kansas Agricultural Experiment Station contribution; no. 93-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 667; Swine; Starter; Performance